Геоінформаційне картографування просторових особливостей міграцій населення України в умовах війни - Джаман, Василь Олексійович; Мельник, Антон Анатолійович; Джаман, Ярослав Васильович (Науковий вісник Чернівецького університету : Географія. Випуск 845, 2023)
Spatial specificities of migrations in population of Ukraine are discussed on the basis of map models (map diagrams, cartograms, map schemes of quantitative background, isolines). Territorial differences in interstate and interregional migrations in the pre-war time, the period of Russia’s hybrid war against Ukraine, and the full-scale war are put under analysis. Destinations and the value of migrant departures/arrivals are disclosed, as well as their effect on the dynamics of population number in Ukraine and its regions.
GIS-Based Mapping of Spatial Specificities of Population Migrations in War-Time Ukraine
Keywords: mapping; GIS technologies; population migration; war; regions; Ukraine